Double-Layered Zirconia Films for Carbon-Based Mesoscopic Perovskite Solar Cells and Photodetectors. (22nd May 2019) - Syrrokostas, George; Leftheriotis, George; Yannopoulos, Spyros N.
Abstract : Carbon-based mesoscopic perovskite solar cells (PSCs) and photodetectors were fabricated with the application of double-layered ZrO2 films, consisting of zirconia nanoparticles and microparticles for the first and the second layer, respectively. This assembly exploits the ability of the zirconia microparticles to scatter and hence diffuse the incident light, causing a more efficient illumination of the perovskite layer. As a result, the photocurrent densities produced by a photodetector and a carbon-based PSC were increased by nearly 35% and 28%, respectively, compared to devices assembled using a conventional single zirconia film. Following the increase in the photocurrent, the responsivity of the photodetector and the power conversion efficiency of the PSC were increased analogously, due to the improved light harvesting efficiency of the perovskite layer. Parameters, such as the total thickness, the roughness, and the crystallinity of the films, were examined. Differences in the grain size and in the crystal planes of the perovskite were observed and evaluated. These results demonstrate that a double-layered ZrO2 film can enhance the efficiency of solar cells and photodetectors, enhancing the prospects for their potential commercialization.